Gastrointestinal causes of sudden unexpected death: A review. (January 2018) - Menezes, Ritesh G.; Ahmed, Saba; Pasha, Syed Bilal; Hussain, Syed Ather; Fatima, Huda; Kharoshah, Magdy A.; Madadin, Mohammed
Gastrointestinal conditions are a less common cause of sudden unexpected death when compared to other conditions such as cardiovascular conditions, but they are equally important. Various congenital and acquired gastrointestinal conditions that have resulted in sudden unexpected death are discussed. The possible lethal mechanisms behind each condition, along with any associated risk factors or secondary diseases, have been described. Through this article, we aim to highlight the need for physicians to prevent death in such conditions by ensuring that subclinical cases are diagnosed correctly before it is too late and by providing timely and efficacious treatment to the patient concerned. In addition, this review would certainly benefit the forensic pathologist while dealing with cases of sudden unexpected death due to gastrointestinal causes. This article is a review of the major gastrointestinal causes of sudden unexpected death. In addition, related fatal cases encountered occasionally in forensic autopsy practice are also included. There are several unusual and rare causes of life-threatening gastrointestinal bleeding that may lead to sudden unexpected death to cover all the entities in detail. Nevertheless, this article is a general guide to the topic of gastrointestinal causes of sudden unexpected death.